FLOURISHING PADA PELUKIS DISABILITAS FISIK YANG TERGABUNG DALAM AMFPA - Natan, Defri Harianto; Kristinawati, Wahyuni (Universitas Kristen Satya Wacana, 2021)
Flourishing is a subjective experience when positive emotion, engagement, positive relationships, meaning and accomplishment combine effectively (Seligman, 2011). Previous research found that engagement is not related to artistic activity (D'raven & Pasha-Zaidi, 2016), even though painting is an artistic experience with a sense of emotion, happiness, etc. (Winarno & Aryanto, 2016). The Association of Mouth and Foot Painting Artists (AMFPA) is an international association of painters with physical disabilities in which painters do not have hands and therefore rely on their mouths or feet when painting. This study aims to describe the flourishing of painters with physical disabilities who [the] are members of AMFPA. The method used in this research is a qualitative method with a phenomenological approach to capture the phenomena experienced by the participants as closely as possible (Smith, 2009). Interviews by telephone (conducted during the Covid-19 pandemic situation) and limited observation were carried out on 3 participants (male, aged 41-54 years) during March - November 2020, only once. Each interview session lasts 90-120 minutes by telephone. The validity of the data was tested using data triangulation, namely interviewing the significant other (Bachri, 2010), such as spouse, siblings and co-workers of the participants. The results of this study indicate that one of the elements of flourishing, namely engagement, is also experienced by painters with physical disabilities. Other findings show that the different backgrounds and experiences of each painter can have an impact on their flourishing experiences.